Transmission of CMV, HTLV-1, and HIV through breastmilk - (:unkn) unknown (My University, 2019)
Breastfeeding is a crucial child survival intervention. However, the potential for transmission of viral infections from mother to child presents the dilemma of how best to interpret the benefits and risks of breastfeeding in different settings. In this Review, we compare the transmission dynamics, risk factors, and outcomes of infection with three chronic viruses transmitted through breastmilk: cytomegalovirus, human T-cell lymphotropic virus type 1, and HIV. We provide an overview of intervention approaches and discuss scientific, policy, and programming gaps in the understanding of these major global infections.
Keywords: African Research